Perilaku Manajemen Keuangan pada Mahasiswa Penerima Program Beasiswa Kartu Indonesia Pintar - Gitayuda, M. Boy Singgih (JURNAL EKBIS, 2023)
The aim of this study was to determine the impact of financial knowledge, financial attitudes, and lifestyle on financial management behavior among college students recipient Kartu Indonesia Pintar - Kuliah (KIP-K) scholarship program at Universitas Trunojoyo Madura. This study was conducted using quantitative associative method. The analysis used is multiple regression analysis on primary and secondary data. The number of respondents used was 88 college students. Sampling techniques use probability sampling methods and simple random sampling approaches. The hypothesis test used is multiple regression analysis using the SPSS 25 program. The results of the t-test show that Financial Knowledge has a partial effect on Financial Management Behavior as evidenced by a significance value of 0.000<0.05, Financial Attitude has a partial effect on Financial Management Behavior as evidenced by a significance value of 0.001<0.05, and Lifestyle has a partial effect on Financial Management Behavior is evidenced by a significance value of 0.008 <0.05.